Modeling face routing in unit disk graphs - Гамаюн, В. П.; Мацуєва, Х. А. (Problems of Informatization and Control, 2015)
The features of using unit disk graphs in modeling face routing are described. The basic geometricalproperties of the interaction of nodes in the unit disk graphs are defined in this article. An algorithmfor calculating the path of packet delivery, which is based on the method of calculating the virtualpath in the virtual plane graphs is proposed